K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 2 2017

mình mới học lớp 6 thôi sorry

1 tháng 2 2017

=\(4x^2-10x-2x+5=\left(4x^2-2x\right)-\left(10x+5\right)\)

=\(2x.\left(2x-1\right)-5.\left(2x-1\right)=\left(2x-5\right).\left(2x-1\right)\)

1 tháng 2 2017

khong biet lam

1 tháng 2 2017

(x3 - 1)(y3 - 1)

= x3(y3 - 1) - (y3 - 1)

= x3y3 - x3 - y3 + 1

hihi

1 tháng 2 2017

a)    x3-x2-21x+45=0

<=> x3+5x2-6x2-30x+9x+45=0

<=> (x+5)(x2-6x+9)=0

<=> (x+5)(x2-3x-3x+9)=0

<=> (x+5)(x-3)2=0

 Vậy S={-5;3}

b)    X3+3X2+4X+2=0

<=>  X3+X2+2X2+2X+2X+2=0

<=> (X+1)(X2+2X+2)=0

VÌ  X2+2X+2 >=0

NÊN S={-1}

C)    X4+7X-8=0

<=> X4-X3+X3-X2+X2-X+8X-8=0

<=> (X-1)(X3+X2+X+8)=0

VÌ X3+X2+X+8>=0

NÊN S={1}

D)     6X4-X3-7X2+X+1=0

<=>  6X4-6X3+5X3-5X2-2X2+2X-X+1=0

<=>  (X-1)(6X3+5X2-2X-1)=0

<=> (X-1)(6X3-3X2+8X2-4X+2X-1)=0

<=> (X-1)(2X-1)(3X2_4X+1)=0

<=>  (X-1)(2X-1)(3X2-3x-x+1)=0

<=> (X-1)2(2X-1)(3x-1)=0

vậy S={1/3;1/2;1}